1979
DOI: 10.1007/bf00498975
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and some properties of biopterin synthase and dihydropterin oxidase from Drosophila melanogaster

Abstract: An enzyme which has been named "biopterin synthase" has been discovered in Drosophila melanogaster. This enzyme, which has been purified 200-fold from extracts of Drosophila, catalyzes the conversion of sepiapterin to dihydrobiopterin, or oxidized sepiapterin to biopterin. The Km values for the two substrates are 63 microM for sepiapterin and 10 microM for oxidized sepiapterin. NADPH is required in this enzymatic reaction. An analysis of enzyme activity during development in Drosophila indicates a correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The oxidation of 7,8-dihydropterin to pterin was shown to be catalyzed by the enzyme dihydropterin oxidase. This enzyme was first purified from D. melanogaster and, though it can use many 7,8-dihydropterin compounds as substrates, the biochemical parameters indicated that its physiological role in D. melanogaster was to participate in the synthesis of isoxanthopterin [40,41] (Figure 6). Among all the D. melanogaster eye-color mutants analyzed, only little isoxanthopterin (lix) did not show any detectable dihydropterin oxidase activity [42].…”
Section: The Isoxanthopterin Branchmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of 7,8-dihydropterin to pterin was shown to be catalyzed by the enzyme dihydropterin oxidase. This enzyme was first purified from D. melanogaster and, though it can use many 7,8-dihydropterin compounds as substrates, the biochemical parameters indicated that its physiological role in D. melanogaster was to participate in the synthesis of isoxanthopterin [40,41] (Figure 6). Among all the D. melanogaster eye-color mutants analyzed, only little isoxanthopterin (lix) did not show any detectable dihydropterin oxidase activity [42].…”
Section: The Isoxanthopterin Branchmentioning
confidence: 99%
“…The oxidation of 7,8-dihydroxanthopterin to the yellow pigment xanthopterin is most likely catalyzed by the enzyme dihydropterin oxidase. This enzyme was first purified from D. melanogaster and was shown to be able to use many 7,8-dihydropterin compounds as substrates [40,41].…”
Section: The Xanthopterin Branchmentioning
confidence: 99%